Hydrothermal Synthesis, Crystal Structure and Optical Property of A 2-D Organic-Inorganic Compound Ni(V2W4O19)(bpy)(Hbpy)2 (bpy = 4,4’-Bipyridine - WANG, CHONG-CHEN (Asian Journal of Chemistry, 2010)
A hydrothermal reaction of NH4VO3, WO3, NiCl2 and 4,4'-bipyridine yields a novel organic-inorganic hybrid compound, Ni(V2W4O19)(bpy) (Hbpy)2 (bpy = 4,4'-bipyridine) (C30H26N6NiO19V2W4, Mr = 1670.56), which was characterized by elemental analysis, IR, single-crystal X-ray diffraction analysis and UV-Vis-NIR diffuse reflectance spectrum. It crystallizes in monoclinic, space group C2/c with a = 19.977(12) Å, b = 11.4602(13) Å, c = 16.0794(18) Å, β = 96.473(2)º, V = 3657.7(7) Å3, Z = 4, Dc = 3.304 Mg/m3, μ = 3.034 mm-1 and F(000) = 3080. The final R = 0.0525 and wR = 0.1552 for 3234 observed reflections with I>2σ(I). In the crystal, each Ni(II) is six-coordinated by two oxygen atoms from two [V2W4O19]4- and two nitrogen atoms from two bidentate bpy ligands and two nitrogen atoms from two protonated and terminal bpy ligands. The title compound is found to have an optical energy gap of 2.3 eV from UV-Vis-NIR diffuse reflectance spectrum.